Wastewater Quality Determines the Quantity of Offsite Sanitation Based on Downstream Standards - Samudro, Ganjar; Samudro, Harida; Mangkoedihardjo, Sarwoko (International Journal of Sustainable Construction Engineering and Technology, 2023)
Offsite sanitation describes the wastewater management in the chain of generation sources to its disposal into the environment. While the user manages the onsite sanitation system for greywater, blackwater requires offsite treatment. In practice, offsite sanitation management implements scoping service areas for centralised, decentralised, and combined hybrid. This study aims to provide feasibility criteria for the offsite sanitation scale and formulate a method compatible with existing methods to accelerate sanitation services. The method used is a downstream approach by assessing the capacity of rivers to receive wastewater discharges. The results consist of river capacity criteria and wastewater quality requirements. The quality load of a river and water dilution ability determine the number of people and the suitability of the sanitation system. The decision-making process in determining the scale of offsite sanitation services directs the problem solution by considering technical, economic, financial, institutional regulations, environmental, and social aspects. Availability of data speeds up problem-solving with effective and efficient use of resources. The core conclusion states that wastewater quality parameters determine the scale of offsite sanitation services.